Effects of different estrus synchronization protocols on reproductive efficiency of indigenous dammar ewes in Yemen - Hezam, Nasser Saleh Obad (2012)
The aim of this study was to compare the effect of different estrus synchronization protocols for long (12 days) and short-term (6 days) on the reproductive efficiency of Dammar ewes during summer and winter in Yemen. A total of 85 ewes were randomly allocated and divided into two experimental groups. The first experiments were conducted for 12 days on those in the long- term (LT) in summer and on those in long-term (LTa) in winter. Similarly, the second experiments were conducted for 6 days on those in short- term (ST) in summer and on those in short- term (STa), in winter. The ewes in (summer, LT) were divided into three subgroups rarely LT1, LT2, and LT3, and in (winter, LTa) were divided into three subgroups rarely LTa1, LTa2 and LTa3 based on eCG 300 IU injecting which were before 48 h, at CIDR removal and control for LT and LTa groups respectively. Whereas the ewes in (summer, ST) group were divided into two subgroups rarely ST1 and ST2. In addition, in winter (STa) group was divided into two subgroups (STa1 and STa2) based on eCG 300 IU injecting which were at CIDR removal and control for ST and STa respectively. The results showed that onset of estrus in groups LT and LTa for 12 day during summer and winter were shorter than the results in groups ST and STa for 6 day, during summer and winter. The results of duration of estrus showed in LT1, LTa1, LT2, LTa2, and ST2 were shorter than the results in STa1, ST1, LT3, STa2 and LTa3. However, the results of cessation of estrus in LTa1, LT1, LT2, LTa2 and LT3 were shorter than the results in those of LTa3, STa1, ST2, STa2 and ST1 there were significant difference (P<0.05) between the 12 day and the 6 day during summer. The result of estrus response, for pregnant and lambing percentages in ewes was 100% in both 12 day and 6 day groups during summer and winter. However, there was no significant difference (P>0.05) between 12 day and 6 day during summer and winter. The litter size in LT1, LT2, LTa2 and LTa1 were higher than in STa1, STa2, ST1, ST2, LT3 and LTa3 there was significant difference (P<0.05) between 12 day and 6 day during summer and winter. The fecundity rates, in LT1, LT2, LTa1 and LTa2 were higher than in the ST2, STa1, ST1, STa2, LT3 and LTa3 there was significant difference (P<0.05) between 12 day and 6 day during summer and winter. However, the twining rates in LT3, LT1, LT2, LTa1 and LTa2 were higher than in LTa3, STa1, STa2, ST1 and ST2 there was significant difference (P<0.05) between 12 day and 6 day during summer and winter. The result of this study indicated that the time of eCG injection had an effect on the litter size but had no effect on the estrus response,pregnancy, lambing, during summer and winter. In conclusion, the results of the present study showed that the short-term (6 days), progesterone treatment in Dammar ewes had a similar effect with the long-term (12 days) to estrus synchronization, pregnancy and lambing rates during summer and winter. Moreover, the litter size in ewes treated by eCG was higher than ewes that were not treated with eCG in both the 12 day and 6 day groups during summer and winter.